Metabolomics analysis of shucked mussels' freshness. (15th August 2016) - Aru, Violetta; Pisano, Maria Barbara; Savorani, Francesco; Engelsen, Søren Balling; Cosentino, Sofia; Cesare Marincola, Flaminia
Highlights: Storage effects on mussels were investigated by metabolomics. The metabolic profile of mussels was analyzed by NMR spectroscopy. Microbial features were characterized. Correlation between metabolites and microbiological counts was investigated. Results confirm metabolomics as a reliable method to assess seafood freshness. Abstract: In this work a NMR metabolomics approach was applied to analyze changes in the metabolic profile of the bivalve mollusk Mytilus galloprovincialis upon storage at 0 °C and 4 °C for 10 and 6 days, respectively. The most significant microbial groups involved in spoilage of mussels were also investigated. The time-related metabolic signature of mussels was analysed by Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) which revealed a clear discrimination between the fresh samples and those stored at 0 °C and 4 °C. The results evidenced a noticeable increase in acetate, lactate, succinate, alanine, branched chain amino acids, trimethylamine and a progressive decline of osmolytes like betaine, homarine and taurine during storage. Exploration of the correlations of these metabolites with microbial counts suggested their use as potential biomarkers of spoilage. The results support the use of NMR metabolomics as a valuable tool to provide information on seafood freshness.